Improvement financial control of metallurgical enterprises in modern conditions - Bobyl, V. V.; Bielikova, T. M. (Science and Transport Progress, 2011)
In this article we analyze the expediency of the financial control at metallurgical enterprises. The problem factors, the solution of which can result in increasing the operational efficiency of metallurgical enterprises are also defined.